2023
DOI: 10.3389/fpls.2023.1141446
|View full text |Cite
|
Sign up to set email alerts
|

MbMYBC1, a M. baccata MYB transcription factor, contribute to cold and drought stress tolerance in transgenic Arabidopsis

Abstract: Cold and drought stress considerably suppress the development of plants. In this study, a new MYB (v-myb avian myeloblastosis viral)TF gene, MbMYBC1, was isolated from the M. baccata and located in nucleus. MbMYBC1 has a positive response to low temperature and drought stress. After being introduced into Arabidopsis thaliana, the physiological indicators of transgenic Arabidopsis had corresponding changes under these two stresses, the activities of catalase (CAT), peroxidase (POD) and superoxide dismutase (SOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…In this study, we analyzed the expression changes of four genes of the CBF transduction pathway in Arabidopsis after low-temperature treatment ( Figure 10 ). It was found that the expression of these four genes was high in transgenic lines, which was consistent with the previous research results [ 17 , 25 , 26 ]. Therefore, it is speculated that FvMYB114 can regulate the expression of cold response genes through the CBF pathway, to improve plant cold tolerance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we analyzed the expression changes of four genes of the CBF transduction pathway in Arabidopsis after low-temperature treatment ( Figure 10 ). It was found that the expression of these four genes was high in transgenic lines, which was consistent with the previous research results [ 17 , 25 , 26 ]. Therefore, it is speculated that FvMYB114 can regulate the expression of cold response genes through the CBF pathway, to improve plant cold tolerance.…”
Section: Discussionsupporting
confidence: 92%
“…Jung et al found that under drought and high salt conditions, the overexpression of AtMYB44 in Arabidopsis could inhibit the expression of negative regulators ( HAB1/2 , AtPP2CA , ABI1 ) in the ABA signal pathway, thus enhancing the tolerance of A. thaliana to drought and salt, so it could grow normally in this vicious environment [ 25 ]. Moreover, MbMYBC1 can promote the expression of cold response genes such as DREB1A , COR15a , ERD10B and COR47 under cold stress [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In such investigations, beyond merely conducting enzymatic reactions or volatile organic compound (VOC) profiling, employing transcriptomics and proteomics techniques allows for the analysis of alterations in gene expression or protein abundance resulting from phytohormone treatments or genetic modifications (Zhu et al, 2019;Yang et al, 2023;Gupta et al, 2024;Hu et al, 2024;Kumari et al, 2024;Xiao et al, 2024). Through this comprehensive approach, researchers can attain a deeper understanding of the molecular mechanisms governing hormone regulation (Liu et al, 2023). This knowledge can then be leveraged through techniques such as RNA interference (RNAi), CRISPR/Cas, overexpressions and/or their combination to engineer plants by altering the expression of enzymes or regulatory genes involved in phytohormone metabolism (Yang et al, 2008;Abe and Ichikawa, 2016;Liu et al, 2023).…”
Section: Integrating Phytohormone For Sustainable Agriculturementioning
confidence: 99%
“…The presence of conserved domains helps researchers predict the roles of U/U genes and provides direction for the functional research of unknown genes. Exogenously overexpressing MbMYBC1 and MbMYB108 from Malus baccata enhanced the cold and drought resistance of transgenic Arabidopsis (Arabidopsis thaliana) (Yao et al, 2022;Liu et al, 2023). Exogenously overexpressing FvMYB82 from strawberry (Fragaria vesca) and the R1-MYB transcription factor gene LcMYB1 from sheepgrass (Leymus chinensis (Trin.)…”
Section: Classification Of U/u Genesmentioning
confidence: 99%